SERUM MARKERS OF APOPTOSIS AND CONVENTIONAL RISK FACTORS IN PATIENTS WITH MYOCARDIAL INFARCTION AND HEALTHY RESIDENTS OF ARKHANGELSK REGION: TRENDS, CAUSES, AND CONSEQUENCES - A. S. Yakovleva; O. A. Mirolyubova; T. V. Supryadkina (Кардиоваскулярная терапия и профилактика)
Aim. To improve the risk stratification in young patients with myocardial infarction (MI), using the data on the Fas-mediated apoptosis activity in early and late post-infarction periods.Material and methods. The study included 28 young MI patients (mean age 42,5±5,6 years), 56 elderly MI patients (mean age 63,0±7,8 years), and 66 healthy volunteers. The following parameters were assessed 2 weeks and 7 months (5,7–10,9 months) after MI: conventional risk factors of coronary heart disease (CHD), lipid profile, electrocardiography, echocardiography, and coronary angiography parameters, the levels of apoptosis biomarkers (sFas, sFasL), Cys C, and BNP-32 (immunoenzymatic method).Results. The mean concentration of sFasL varied by gender, reaching 65,09±36,95 pg/ml in women vs. 77,27±27,48 pg/ml in men (р=0,008). The levels of sFasL were higher in young MI patients (80,18±40,54 pg/ ml), compared to healthy volunteers (58,38±25,79 pg/ml; р=0,012), while there was no marked variation in the levels of sFas. Smoking was associated with higher sFas levels. The concentration of sFasL was associated with the levels of blood lipids, fibrinogen, and body mass index. Patients with arterial hypertension had a higher concentration of sFasL (81,80±37,98 pg/ml) than their non-hypertensive peers (55,30±11,96 pg/ml; р=0,029). The sFas/sFasL ratio was linked to the number of metabolic syndrome (MS) components. Among young MI patients, the levels of sFasL, measured 2 weeks after MI, could be used for the prediction of a new coronary event in the next 6–8 months (sensitivity 75% and specificity 90%).Conclusion. The concentration of sFasL was higher in young MI patients than in healthy individuals. The levels of sFasL were inversely associated with the number of MS components and also demonstrated predictive value for the assessment of the 6–8-month risk of recurrent angina in young MI patients.